2015
DOI: 10.1128/jvi.00464-15
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral Cyclin Controls Cyclin-Dependent Kinase 8-Mediated Transcription Elongation and Reinitiation

Abstract: Walleye dermal sarcoma virus (WDSV) infection is associated with the seasonal development and regression of walleye dermal sarcoma. Previous work showed that the retroviral cyclin (RV-cyclin), encoded by WDSV, has separable cyclin box and transcription activation domains. It binds to cyclin-dependent kinase 8 (CDK8) and enhances its kinase activity. CDK8 is evolutionarily conserved and is frequently overexpressed in human cancers. It is normally activated by cyclin C and is required for transcription elongatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 87 publications
(172 reference statements)
1
13
0
Order By: Relevance
“…More investigation into the global picture of CDK8/19-regulated gene expression during DENV2 infection is warranted to understand their complete role. We previously showed that CDK8 activity is enhanced by a retroviral cyclin [31,32,35]. Interaction between the retroviral cyclin and CDK8 enhances CDK8 function in the serum response to the advantage of the virus, which requires cell proliferation for transmission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More investigation into the global picture of CDK8/19-regulated gene expression during DENV2 infection is warranted to understand their complete role. We previously showed that CDK8 activity is enhanced by a retroviral cyclin [31,32,35]. Interaction between the retroviral cyclin and CDK8 enhances CDK8 function in the serum response to the advantage of the virus, which requires cell proliferation for transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of either CDK8 or CDK19 has previously been shown to reduce the proliferation rate of cultured cells [31,54,55], and we observed reduced proliferation of CDK8 and CDK19 These data demonstrate that CDK8 mRNA and protein levels increase after DENV2 infection and suggest active CDK8 phosphorylation of histone H3 at serine 10 in association with increased transcriptional activity. CDK8 chromatin occupancy is also increased during DENV2 infection, an outcome associated with enhanced CDK8-dependent gene expression [27,28,31,32].…”
Section: Knockdowns Of Cdk8 and Cdk19 Reduce Denv2 Replicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Forward primer Reverse primer GAPDH (95) 5=-GCCATCAATGACCCCCAT-3= 5=-CGCTCCTGGAAGATGGTG-3= ␣0 5 =-CCCACTATCAGGTACACCAGCTT-3= 5=-CTGCGCTGCGACACCTT-3= UL54 5=-GCATCCTTCGTGTTTGTCATTCTG-3= 5=-GCATCTTCTCTCCGACCCCG-3= UL29 5=-GGGCGCAACTTTCGCAATCAATTC-3= 5=-GGCCGACAGAAACCCGTTGTTAAA-3= UL51 5=-GCCAGTCGTTCTAGGTTCAC-3= 5=-GTTAACGCGCTACTTCCCG-3= UL31 5=-GGTCTATGAGCCGGTAGTGC-3= 5=-CTCTTGGCCGGGATTCTTGG-3=…”
Section: Targetmentioning
confidence: 99%